The DegU Orphan Response Regulator Contributes to Heat Stress Resistance in Listeria monocytogenes - Cheng, Changyong; Liu, Feng; Jin, Haobo; Xu, Xiangfei; Xu, Jiali; Deng, Simin; Xia, Jing; Han, Yue; Lei, Lei; Zhang, Xian; Song, Houhui (Frontiers in Cellular and Infection Microbiology, 2021)
Listeria monocytogenes is more heat-resistant than most other non-spore-forming foodborne pathogens, posing a severe threat to food safety and human health, particularly during chilled food processing. The DegU orphan response regulator is known to control heat resistance in L. monocytogenes; however, the underlying regulatory mechanism is poorly understood. Here, we show that DegU contributes to L. monocytogenes exponential growth under mild heat-shock stress. We further demonstrate that DegU directly senses heat stress through autoregulation and upregulates the hrcA-grpE-dnaK-dnaJ operon, leading to increased production of heat-shock proteins. We also show that DegU can directly regulate the expression of the hrcA-grpE-dnaK-dnaJ operon. In conclusion, our results shed light on the regulatory mechanisms underlying how DegU directly activates the hrcA-grpE-dnaK-dnaJ operon, thereby regulating heat resistance in L. monocytogenes.